Perception Of Prescription Drug Abuse Among Medical Students - Mathur, Akshit; Singh Rajawat, Aditya Pratap; Khan, Sania Fatima; Ranjan, Amol; Parida, Truptimayee; Mishra, Atulya Vedanta; Singh, Sapna; Dalavi, Rupesh Dinakar; Kumar Garg, Hemant; Mohan, Brij (Journal of Neonatal Surgery, 2025)
Prescription drug abuse is a rising public health challenge, especially among populations with early exposure to pharmacological education. This cross-sectional study evaluated perceptions, attitudes, and self-reported practices related to prescription drug misuse among 100 medical students from three tertiary institutions in India. A validated 24-item Likert-scale questionnaire (Cronbach’s α = 0.84) revealed moderate awareness but significant misconceptions regarding non-medical use of prescription drugs. Misuse was frequently rationalized under academic stress and cognitive performance pressure. Statistical analysis using chi-square and logistic regression showed a significant association between perceived safety and self-use (χ² = 14.8, p < 0.001), with high academic stress emerging as a key predictor (OR = 1.73, 95% CI: 1.2–2.4). Findings call for integrated pharmacovigilance, ethics modules, and mental health support in the medical curriculum